The Role of Intelligence in Countering Terrorism in Indonesia - Nudan, Pankrasius Wahu; Widodo, Pujo; Afifuddin, Mochammmad (CV. Rayyan Dwi Bharata, 2025)
National intelligence is at the forefront of the national security discourse. One of the main threats to national security today is the threat of terrorism. Intelligence as information, process, mission, and organization is very important in the effort to combat terrorism in Indonesia. The author attempts to answer the question of how intelligence plays a role in combating terrorism in Indonesia. The research approach used is a qualitative approach using secondary data sources. The results of the study show that; First, intelligence as information must provide accurate intelligence information related to terrorism because this will be one of the main considerations in policy making. Second, intelligence as a process must go through the appropriate intelligence cycle. Third, intelligence and counterintelligence missions must be carried out professionally in terms of both human resources and equipment used, following the development of the Revolution in Intelligence Affairs. Fourth, existing intelligence organizations must be able to improve coordination and cooperation in order to implement terrorism prevention optimally.